2012
DOI: 10.1097/jsm.0b013e318257a40b
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Reported Knee Function and Health-Related Quality of Life After Knee Injury in Female Athletes

Abstract: In addition to negatively affecting knee function, sport medicine providers should be aware that knee injuries can negatively impact the health-related quality of life in these athletes immediately after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Within-study comparisons between retrospectively collected pre-injury HRQL and general population norms indicated that self-reported pre-injury HRQL scores were consistently higher than population norm scores ( n  = 3) [8, 29, 48]. Three studies found that scores were higher in either the physical domains ( n  = 3) [20, 21, 28] or mental domains ( n  = 1) [20] or in certain age or sex groups ( n  = 1) [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within-study comparisons between retrospectively collected pre-injury HRQL and general population norms indicated that self-reported pre-injury HRQL scores were consistently higher than population norm scores ( n  = 3) [8, 29, 48]. Three studies found that scores were higher in either the physical domains ( n  = 3) [20, 21, 28] or mental domains ( n  = 1) [20] or in certain age or sex groups ( n  = 1) [6].…”
Section: Resultsmentioning
confidence: 99%
“…1 Adjusted by the age and sex distribution in the study population, based on the weighted health state index by age and sex [13, 14]. 2 Final post-injury measurement: at 3 [27], 6 [43] or maximal 9 months post-injury [18], 1 year post-injury [26, 28, 29, 32, 33, 48], 2 years post-injury [44], or 4 – 8 years post-injury [46]. Heterogeneity: PCS Chi 2  = 12.48, df = 11, ( p  = 0.33), I 2  = 12%; MCS Chi 2  = 11.88, df = 11, ( p  = 0.37), I 2  = 7%.…”
Section: Resultsmentioning
confidence: 99%
“…After a significant time loss injury, athletes can suffer physically as well as emotionally with a decrease in quality of life measures 38 39. The emotional response to an ACL injury can be more significant than that experienced after concussion 40.…”
Section: Injuries: Problematic Responsesmentioning
confidence: 99%
“…This effect has been demonstrated in joint replacement and spine disease as well as in a number of upper extremity disease states. 1,2,4,9,11,12,[18][19][20][21][22]25,29,30 In some cases, behavioral health interventions are even being offered in conjunction with treatment of the orthopedic condition or as a precondition for surgical treatment. 2,7 In the shoulder, numerous studies have documented the profound impact of biopsychosocial stressors, coping mechanisms, and pain catastrophizing on perception of shoulder pain and disability.…”
mentioning
confidence: 99%